Unveiling the uncommon occurrence in an unexplored area: a case report of successfully treated primary upper extremity deep venous thrombosis with a review of the literature - Tammi Raju Iragavarapu; Sahitya Chennapragada; Sushma Vutukuru (Veins and Lymphatics)
Upper Extremity Deep Vein Thrombosis (UEDVT), though less prevalent than its lower extremity counterpart, poses a substantial risk of morbidity and mortality, particularly among patients in intensive care units. We present a case of Primary Upper Extremity UEDVT in the dominant limb of a 22-year-old female, a software employee. She presented to the hospital with a history of swelling and pain in her right upper limb for 3 months. After several consultations, she sought medical advice at our hospital for her long-lasting symptoms. Doppler study showed a dilated right subclavian vein/ axillary vein with echogenic thrombus, and these vessels are non-compressible. CT venography of the right upper limb confirmed a long segment thrombus in the right subclavian vein from its origin, filling the axillary vein and brachial veins to the level of the upper third of the arm. After excluding all other secondary causes, a diagnosis of primary UEDVT was made. Then, the patient was subsequently started on anticoagulant therapy, and after 3 months of anticoagulation therapy, she was successfully cured of thrombosis. A high index of suspicion is required for early recognition and treatment of UEDVT to prevent complications such as post-thrombotic syndrome, and pulmonary embolism.